Survey article: Multiculturalism as fairness: Will Kymlicka's multicultural citizenship - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 2002)
According to Will Kymlicka's book Multicultural Citizenship: A Liberal Theory of Minority Rights, `the liberal ideal is a society of free and equalindividuals'.1 But what, he goes on to ask, is the relevant `society'? The answer he says most people would give is `their nation'. `The sort of freedom and equality they most value, and can make use of is freedom and equality within their own societal culture'. Indeed, most people `are willing to forgo a wider freedom and equality to ensure the continued existence of their nation' (93). Thus few favour open borders which allow people freely to settle, work and vote in whatever country they wish, for while this would greatly expand the domain of freedom and equality, it would also increase the likelihood of their country being overrun by settlers from other cultures, thereby endangering their own survival as adistinct national culture. Most people favour `decreased mobility but a greaterassurance that people can continue to be free and equal members of their own national culture' (93). Kymlicka concurs, and he also suggests that `most theorists in the liberal tradition have implicitly agreed with this' (93). Like John Rawls, liberal theorists (according to Kymlicka) assume that people are born and are expected to lead a complete life within the same society and culture, and assume that this defines the scope within which people must be free and equal. To put it more bluntly, `most liberals are liberal nationalists'.